Estimations of high-temperature diffusion in Chernobyl’s concrete construction - Dikiy, N.P.; Dedik, A.N.; Dovbnya, A.N.; Uvarov, V.L. (Вопросы атомной науки и техники, 2005)
The content of isotopes Ti, Ni, Zr, Cs and U in the cores, which was taken from the concrete construction of ChAPS, was studied by the gamma-activation analysis. It has been developed a numerical model to analyze heat and mass transfer in concrete at high temperatures accompanying incident of 1986. Comparison of the measured isotope distributions with the simulation data has enabled to estimate some attendant circumstances of the incident. Методом гама-активаційного аналізу вимірювався зміст ізотопів Ti, Ni, Zr, Cs та U у кернах, відібраних з бетонної конструкції ЧАЕС. Розроблено числову модель для аналізу переносу тепла та маси у бетоні при високих температурах, що супроводжували катастрофу 1986 року. Порівняння виміряних ізотопних розподілів з результатами модельних розрахунків дало можливість зробити оцінки деяких характеристик інциденту, що стався. Методом гамма-активационного анализа измерялось содержание изотопов Ti, Ni, Zr, Cs и U в кернах, отобранных из бетонной конструкции ЧАЭС. Разработана численная модель для анализа тепло- и массопере- носа в бетоне при высоких температурах, сопровождавших катастрофу 1986 года. Сравнение измеренных изотопных распределений с результатами модельных расчетов дало возможность сделать оценки некоторых характеристик происшедшего инцидента.